Numerical analysis on heat transfer of a pyramid-shaped photovoltaic panel - Abu-Hamdeh, Nidal H.; Khorasani, Saleh; Öztop, Hakan Fehmi; Alnefaie, Khalid A. (Springer, 2022)
In the present study, a pyramid-shaped solar panel as a novel design of a photovoltaic (PV) panel is simulated. The simulation process was performed by means of an open source CFD software (Open foam, Version 2.3.1). Also, the Bouyant Boussinesq Pimple Foam solver was used in this study. In this study, four PVs were fabricated in the form of pyramid-shaped construction with trapdoors at the bottom and topsides which were assumed as the inlet and outlet of the coolant air, respectively. The flow was considered to be steady. The inlet velocity is chosen as a governor parameter on heat and fluid flow. Three inlet velocities of 0.01 ms(-1), 0.1 ms(-1), and 1 ms(-1) with constant inlet temperature of 293 K were considered to check the effect of inlet velocity on the cooling of the PVs. For each air velocity, three different heat flux values of 250, 500, and 750 Wm(-2) were considered to simulate the effect of different time periods of the day. The results presented that by the increment of air mass flow rate, the flow patterns of air flow change from buoyancy induced flow to forced flow causing to creation of small vortices at the corners of the pyramid which result in augmentation of heat transfer coefficients in this regions. The increment of the inlet air velocity increases the heat transfer coefficient up to 1.9 times which leads in reduction of backside temperature of the PVs. It was found that the increment of air velocity could lead in up to 29% reduction in the backside temperature difference. When the inlet velocity of air stream was equal to 1 ms(-1), the backside temperature of the panel faced 42 K lower temperature than that associated with the inlet velocity of 0.01 ms(-1).
Keywords: Novel PV design; Heat transfer; Pyramid; Solar energy; Photovoltaic cooling